HASIL PERANCANGAN MODUL KALKULUS DASAR DAN LANJUT DENGAN MENGGUNAKAN MAPLE 14 - Isra Nurmai Yenti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2016)
AbstractThis research aims at producing the module design of basic and advanced calculus using Maple 14 in mathematics computer application course. This research used research and development. The module was developed by modifying the previous module as designed by Rahman (2013). The stages applied refers to Akker and Plom (1994). The module consists of three units – introduction, learning activities, and closing. Based on the findings, this module could be used in teaching mathematics computer application subject.Kata Kunci: modul, Maple 14, kalkulus dasar dan lanjut.